A pulsed mode electrolytic drug delivery device. (14th September 2015) - Yi, Ying; Buttner, Ulrich; Carreno, Armando A A; Conchouso, David; Foulds, Ian G
Abstract: This paper reports the design of a proof-of-concept drug delivery device that is actuated using the bubbles formed during electrolysis. The device uses a platinum (Pt) coated nickel (Ni) metal foam and a solid drug in reservoir (SDR) approach to improve the device's performance. This electrochemically-driven pump has many features that are unlike conventional drug delivery devices: it is capable of pumping periodically and being refilled automatically; it features drug release control; and it enables targeted delivery. Pt-coated metal foam is used as a catalytic reforming element, which reduces the period of each delivery cycle. Two methods were used for fabricating the Pt-coated metal: sputtering and electroplating. Of these two methods, the sputtered Pt-coated metal foam has a higher pumping rate; it also has a comparable recombination rate when compared to the electroplated Pt-coated metal foam. The only drawback of this catalytic reformer is that it consumes nickel scaffold. Considering long-term applications, the electroplated Pt metal foam was selected for drug delivery, where a controlled drug release rate of 2.2 μ g  ±  0.3 μ g per actuation pulse was achieved using 4 mW of power.